2003
DOI: 10.1097/00005721-200303000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Media Images, Body Dissatisfaction, and Disordered Eating in Adolescent Women

Abstract: This article examines the literature related to the media, body image, and diet/weight issues in children and young women. The media holds an awesome power to influence young women, bombarding them with images of abnormally thin models who seem to represent the ideal. When the majority of adolescents inevitably fail to achieve the extremely thin image they crave, body dissatisfaction results, and disordered eating can begin. Emerging research in the pediatric and adolescent literature demonstrates that childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…2 Boys' body dissatisfaction has simultaneously increased, 4 and research has demonstrated that exposure to images of extremely muscular models contributes to body dissatisfaction and muscle dysmorphia in young men. [5][6][7] Research regarding media images of women has focused almost exclusively on thinness as the cultural ideal for femininity, 8,9 but there is some indication that modern media figures combine slenderness with a toned and firm look that was not emphasized in previous generations. [10][11][12] Muscle-enhancing behaviors have received considerable attention in the media and popular culture in recent years, as a steady stream of famous male and female athletes have been implicated in legal cases regarding their alleged use of performanceenhancing substances.…”
Section: Discussionmentioning
confidence: 99%
“…2 Boys' body dissatisfaction has simultaneously increased, 4 and research has demonstrated that exposure to images of extremely muscular models contributes to body dissatisfaction and muscle dysmorphia in young men. [5][6][7] Research regarding media images of women has focused almost exclusively on thinness as the cultural ideal for femininity, 8,9 but there is some indication that modern media figures combine slenderness with a toned and firm look that was not emphasized in previous generations. [10][11][12] Muscle-enhancing behaviors have received considerable attention in the media and popular culture in recent years, as a steady stream of famous male and female athletes have been implicated in legal cases regarding their alleged use of performanceenhancing substances.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that the majority of disturbances in body perception start during adolescence, a period of rapid physiological changes [33]. In our previous work, waist circumference (WC) was found to correlate more closely with body perception than BMI in adolescent girls [7], implicating that body fat distribution mediates body size estimation.…”
Section: Discussionmentioning
confidence: 94%
“…Pollack, 2003;Groulez, 2006;Tierney, 2006Tierney, , 2008 and empirical studies (Mulveen & Hepworth, 2006), online ethnography (Brotsky & Giles, 2007), and grounded theory (Norris et al, 2006;Williams & Reid, 2007). 9) A closely related differentiation is drawn between a micro approach, which seeks to render a thick description of motivations, actions, and behaviours at the individual level (as in ethnography), and a macro approach, with focus on social structures at the group or system level (Andrist, 2003;Eichenberg & Brähler, 2007;Ward, 2007). 10) Among empirical studies, the vast majority employ some form of content analysis or passive observation of websites considered as ‗naturally occurring discourse' (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…While early analyses of pro-ED websites (Dias, 2003;Ferreday, 2003;Pollack, 2003;Regan Shade, 2003;Fox et al 2005;Da Cunha Recuero, 2005;Martin, 2005) were primarily socio-cultural, the second half of the decade has seen the rise of the share of health-sciences contributions. Before 2005, clinical studies were indeed present with a mere three short papers (Andrist, 2003;Davies & Lipsey, 2003;Chesley et al, 2003), and only after that date were the first strong results produced, with the contributions of, among others, Bardone-Cone & Cass 2) Among the articles adopting a socio-cultural approach, some pursue the feminist and poststructuralist tradition of presenting eating disorders as a gender-aware critical stance against biomedical power. This view has a more radical flavour in earlier articles (Dias, 2003;Ferreday, 2003;Pollack, 2003) and appears nuanced in recent ones, as emphasis has gradually shifted to a more multifaceted representation of the phenomenon, taking into account both biological and cultural factors (Mulveen & Hepworth, 2006;Ward, 2007;Overbeke, 2008).…”
Section: Epistemological Approachesmentioning
confidence: 99%